Laboratory predictors of strangulation in patients with inguinal hernia - Mozafar, Mohamad; Ghaderzadeh, Pezhman; Kasraianfard, Amir (Researcher Bulletin of Medical Sciences, 2025)
Objective: The diagnosis of strangulated hernias cases prior to surgery remains to be a challenging issue. Various diagnostic tests can be used in these patients. Hence, we aimed to evaluate the diagnostic value of leukocytosis, left shift, and ABG in the diagnosis of strangulated cases with incarcerated inguinal hernia. Materials and Methods: 107 males and 2 females were enrolled in the study. Medical records of emergency hernia operation cases from March, 2016 up to March, 2021, have been evaluated. Preoperative data such as blood tests, medical history, and surgical outcomes were recorded. Results: Age was higher in the strangulated and incarcerated group. The rate of involvement of the small intestine, the duration of more than 6 hours from the onset of symptoms to surgery, and enlarged prostate size in patients in the strangulated group were higher. Evaluation of WBC, neutrophils, platelets count, and neutrophil to lymphocyte ratio blood levels showed that, except for platelets blood levels, other biomarkers were significantly higher in the strangulated-incarcerated group. The sensitivity of the tests were 0.84, 0.85, and 0.84, respectively. Also, the diagnostic value cut-off points of each of the tests were 9150-9250, 81-84, and 4.71-4.94, respectively. Conclusion: The results of the present study showed that, the ratio of neutrophils to lymphocytes, neutrophils, and WBC count can be good predictors of strangulated hernia.